EDUKASI TENTANG TATA KELOLA KEUANGAN DI DESTINASI WISATA MAKAM WALI PITU DESA KAMPUNG KUSAMBA, KABUPATEN KLUNGKUNG, BALI - Ida Bagus Teddy Prianthara; Ketut Bayu Agung Suwiyoga Tangkas; I Putu Dharmawan Pradhana; Sahri Aflah Ramadiansyah; I Gusti Ayu Wirati Adriati (Bajang Institute, 2025)
Kampung Kusamba Village is one of the villages located in Klungkung Regency, Bali which has a goal of being a tourist village. With the support of having a lot of tourism potential in the village, of course this village can become a tourist destination for the people of Indonesia, one of the tourism potentials in the Kampung Kusamba village is religious tourism of the Makam Wali Pitu. The Purpose of education on financial governance is to provide knowledge and skills regarding financial governance to the administrators of the Makam Wali Pitu through training in improving financial management